2005
DOI: 10.5194/acp-5-799-2005
|View full text |Cite
|
Sign up to set email alerts
|

A review of biomass burning emissions part II: intensive physical properties of biomass burning particles

Abstract: Abstract. The last decade has seen tremendous advances in atmospheric aerosol particle research that is often performed in the context of climate and global change science. Biomass burning, one of the largest sources of accumulation mode particles globally, has been closely studied for its radiative, geochemical, and dynamic impacts. These studies have taken many forms including laboratory burns, in situ experiments, remote sensing, and modeling. While the differing perspectives of these studies have ultimatel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

106
1,226
9
12

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,228 publications
(1,390 citation statements)
references
References 113 publications
106
1,226
9
12
Order By: Relevance
“…The high sulfate and low anthropogenic elements can be used to distinguish these data from that featuring coal-burning aerosol. Similarly, biomass burning originated aerosols contain high levels of potassium, organic carbon and black carbon, and the aerosols are predominantly in the fine mode (Reid et al, 2005). Through a reasonable procedure of remote sensing-assisted data training, our method can be applied to identify a number of distinct aerosol sources in research and regulatory applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high sulfate and low anthropogenic elements can be used to distinguish these data from that featuring coal-burning aerosol. Similarly, biomass burning originated aerosols contain high levels of potassium, organic carbon and black carbon, and the aerosols are predominantly in the fine mode (Reid et al, 2005). Through a reasonable procedure of remote sensing-assisted data training, our method can be applied to identify a number of distinct aerosol sources in research and regulatory applications.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that we consider all dust emissions from North America, including these from the Chihuahuan Desert in Mexico as local dust because the southern Chihuahuan Desert is a frequent dust source for aerosols in the southwestern US, especially Texas and New Mexico. The low PM 2.5 /PM 10 ratio is also expected to exclude high PM concentration contributed by biomass burning, which is dominated by fine particles, resulting in a high PM 2.5 /PM 10 ratio (Reid et al, 2005). A simple sensitivity test was conducted in the Discussion section to examine how sensitive the results are to the choice of the cutoff value.…”
Section: Approach To Identify Local Dust Recordsmentioning
confidence: 99%
“…power law function (absorption = C × λ -AAE ) and thus the AAE determined with any wavelength pair can be used to approximately calculate the shape of absorption across the UV-VIS range (Reid et al, 2005). We sampled a total of 75 stack burns and 32 room burns at the FSL combustion facility during October and November 2016.…”
mentioning
confidence: 99%
“…Burkart et al (2010) found that the C-factor can be estimated as the ratio of the instrument-30 specific factor to the aerosol density. Accordingly, assuming that the typical density of BB aerosol is about 1.3 g cm −3 (Reid et al, 2005b), we estimated the C-factor for our case to be of 1.27. Measurements of the CO mixing ratio were made with a modified commercial gas analyzer Thermo 48C (Thermo Environmental Instruments, USA; see Nédélec et al, 2003;Paris et al, 2008).…”
Section: Aircraft Measurements 25mentioning
confidence: 99%
“…30 The aerosol particles of all types were distributed among ten size bins covering the particle diameters from 10 nm to 40 µm following a lognormal size distributions. Based on an empirical BB particle emission model by Reid et al (2005b) emissions of BC and OC from fires were distributed among a range of particle sizes using a lognormal particle size distribution with a mass mean diameter of 0.3 µm and a geometric standard deviation of 1.6. Usually a minor fraction of BB emissions, which comprises coarse particles with a typical mean diameter of about 5 µm, was disregarded in our simulations.…”
Section: Simulations With the Chimere Modelmentioning
confidence: 99%